PENDIDIKAN KARAKTER ANAK STASI CAREP, PAROKI ST. MIKHAEL KUMBA MELALUI KEGIATAN SERIKAT KERASULAN ANAK MISIONER - Bule Oswaldus; Maria Margareta Prada; Armina Amul (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
The development of children into healthy individuals and having good characters is a challenge for educators at all times. Educators in families, schools, and communities have an important role in educating children's characters. This paper was written based on community service activities carried out at Carep Station, St. Michael Parish of Kumba, Ruteng. There was found the problem of the character of the children. There were children who are lack of basic trust, sense of independence, initiative, creativity, and perseverance; they suffered from inferiority complex, speak dirty words, do not behave properly during the liturgy in the Church; they do not have care for nature as a common home and have not fully understood the values of the Scriptures. Therefore, the activities of the Missionary Children's Apostolic Union were carried out to educate the values ​​of good character. The methods applied are prayer, reading and explaining the text of the Bible, dramatizing the story of the Bible, singing, dancing, drawing, the practice of cleaning the church and its surroundings as well as explanations about the equipment of the church. The result of the activities showed that the children were active and enthuastic to participate and are making progress in living values such as basic trust, initiative, creativity, and perseverence; they are more confident and polite; they start to love the natural environment and develop proper behavior during the liturgical celebration and appreciate the Word of God. This activity is recommended to be carried out on an ongoing basis for the children of the Carep station and children in other places